“It can cry, it can speak, it can pee”: Modality values and playing affordances in contemporary baby dolls’ discourse - Danielle Almeida (Ilha do Desterro)
Baby dolls have been in the toy market for more than a hundred years, since French firm Jumeau entered the toy industry in the 19th century and started producing ‘bébés’, considered the greatest phenomena of the toy market (FLEMING, 1996). The aim of this analysis is to shed some light on the multimodal properties provided by the aural, verbal and visual texts of the packages of Brazilian baby dolls through a careful look at their textual and contextual meanings, anchored on Kress & Van Leeuwen’s (2006) subsystem of modality (reality value), within the interpersonal visual metafunction. The analyses of the baby dolls’ packages point to roles suggested to young girls from very early age, varying from parenting roles they are asked to fullfill later in life as future mothers to medical abilities they are encouraged to master in order to care and nurture for their “children”.